INOVASI PEMBUATAN LEMBAR KERJA PESERTA DIDIK ELEKTRONIK (E-LKPD) MENGGUNAKAN LIVEWORKSHEET - Fachrul Rozi; Lisa Utami (Journal of Chemistry Education and Integration, 2023)
AbstractLearn from covid-19 pandemic, It is necessary to renew, adjust, and improve teaching and learning activities in schools. One of them is by utilizing and developing learning media based on technology that can show various microscopic and abstract concepts that are difficult to display or visualize directly, namely interactive worksheets based on live worksheets. This research was carried out in the 2021/2022 academic year at Senior High School Muhammadiyah Pekanbaru with the main material being is acid-base. The method of this research used was ADDIE (Analysis, Design, Development, Implementation, Evaluation) modeling with limitation up to the implementation stage only. The data taken in this research were in the form of literature studies, interviews, and questionnaires. The data collection instrument of this research was in the form of validity questionnaires and responses questionnaires data. The data obtained were then analyzed using qualitative descriptive analysis and quantitative descriptive analysis techniques. Interactive students worksheets based on the live worksheets on acid-base materials had been tested to be very valid with a percentage of 88.93% from media experts and 82,44% from material experts and got very good response from students with percentage of 92,66%. Based on these results it can be concluded that interactive student worksheets based on live worksheets on acid - base materials are declared to be valid and reliable so that this media is suitable to be applied in the learning process.Keywords : Acid Base, Liveworksheet, E-LKPD